Determinar el estado nutricional de adultos mayores que habitan en la I etapa - pueblo joven Los Laureles - distrito del Porvenir, empleando medidas antropométricas durante el mes de junio del 2011.” - Tapia Bardales, Roxana Lizeth (2012)
In Peru, there is little information on the nutritional status of elderly so the purpose of this study is to assess the nutritional status of elderly living in the shantytown Los Laureles, through an anthropometric evaluation and determining whether the age, gender and location of the patient have any significant effect on this analysis. The study included 60 older adults between 60 and 92 years, residents of Los Laureles young people - Porvenir who were chosen at random. Data were collected through an survey, and thus unable to determine the body mass index (BMI), waist - hip, complexion and skin folds. We found a favorable nutritional status, energy consumption was not satisfactory in most of the elderly (65%), and was in critical condition for 12% of them. It indicates the need for further studies to characterize the nutritional problems of this population group